ANALISIS PENGARUH FAKTOR LINGKUNGAN EKSTERNAL TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE LAYAR SENTUH MEREK SAMSUNG DI KALANGAN MAHASISWA FE UNISMA - Lailasari Lailasari; Muhammad Hufron; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTPhenomenon of Handphone touch screen in Indonesia become a requirement not only as complement of life style, but as requirement in assisting everyday activity like in have business and support activity of lecturing. Therefore, decision of purchasing of consumer to product of handphone touch screen very require to be paid attention from factor facet of eksternal because by research, hence evaluation pasca purchasing happened. Target this research is to know influence cultural, social class, reference group and family by simultan and parsial to decision purchasing of handphone touch screen environment Student of Faculty Economics Islamic University of Malang. Result of research indicate that cultural variable, social class, reference group, family have an effect on by simultan to decision purchasing of handphone touch screen Samsung brand. While variable cultural, social class, reference group, family by parsial have an effect to decision purchasing of handphone touch screen Samsung brand.Keyword: factor of external and decision purchasing